2003
DOI: 10.1023/a:1024854101965
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The SAP domain is a recently defined DNA binding domain that forms a helix-extended-helix structure. SAP proteins have been implicated in nuclear architecture and/or RNA metabolism. In this paper, we describe the cloning and characterization of a rice gene, OsBP-73, encoding a 375 amino acid protein with a SAP-like domain. We identified the binding sequence of OsBP-73 by gel retardation assays and southwestern blotting. Northern blot analysis demonstrated that OsBP-73 is weakly expressed in root, leaf and imma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Closer examination of the region showed that it sits between the dwarf gene OsBP-73 (Os03g0183100) and a plant height gene TIFY11b (Os03g0181100), which are located ~21 kb upstream and ~84 kb downstream, respectively. The dwarf gene OsBP-73 inhibits plant growth by reducing tiller number and panicle number and shortening culms (Chen et al, 2003), whereas TIFY11b increases plant height and increases seed size by pronounced accumulation of stem carbohydrates (Nakamura et al, 2007;Hakata et al, 2012). Previous studies have reported similar pleiotropic observations between HD and grain length in a chromosomal region; an example of this is the Ghd8 gene, which affects grain yield, HD, and PHt (Yan et al, 2011).…”
Section: Genome-wide Association Analysis Of the Rcs Diversity Panelmentioning
confidence: 72%
“…Closer examination of the region showed that it sits between the dwarf gene OsBP-73 (Os03g0183100) and a plant height gene TIFY11b (Os03g0181100), which are located ~21 kb upstream and ~84 kb downstream, respectively. The dwarf gene OsBP-73 inhibits plant growth by reducing tiller number and panicle number and shortening culms (Chen et al, 2003), whereas TIFY11b increases plant height and increases seed size by pronounced accumulation of stem carbohydrates (Nakamura et al, 2007;Hakata et al, 2012). Previous studies have reported similar pleiotropic observations between HD and grain length in a chromosomal region; an example of this is the Ghd8 gene, which affects grain yield, HD, and PHt (Yan et al, 2011).…”
Section: Genome-wide Association Analysis Of the Rcs Diversity Panelmentioning
confidence: 72%
“…The previously described rice protein OsBP-73 (Os03g0183100) was assumed to bind DNA (44) and exhibits 35% sequence similarity to the N-terminal part of RHON1. An in vitro interaction with the promoter of the nuclear waxy gene in rice suggested localization of OsBP-73 in the nucleus where it functions as transcription factor.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, experiments performed on transgenic rice plants containing a 3-glucuronidase (GUS) reporter gene controlled by the Wx promoter with the 31 bp sequence present synthesized 2-3 times the amount of GUS as plants carrying the reporter gene and a Wx promoter with the 31 bp sequence deleted. These results indicated that the 31 bp sequence plays an important role in the transcriptional regulation of the rice Wx gene (Chen et al 2003a;Yang et al 2002;Zhu et al 2003).…”
Section: Cloning and Functional Identification Of Genes Of Agronomic mentioning
confidence: 78%